1999
DOI: 10.1074/jbc.274.52.37226
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Matrix Metalloproteinase Complex Formation on the Conformational Mobility of Tissue Inhibitor of Metalloproteinases-2 (TIMP-2)

Abstract: The backbone mobility of the N-terminal domain of tissue inhibitor of metalloproteinases-2 (N-TIMP-2) was determined both for the free protein and when bound to the catalytic domain of matrix metalloproteinase-3 (N-MMP-3). Regions of the protein with internal motion were identified by comparison of the T 1 and T 2 relaxation times and 1 H-15 N nuclear Overhauser effect values for the backbone amide 15 N signals for each residue in the sequence. This analysis revealed rapid internal motion on the picosecond to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…This finding further supports our previous suggestion that although the position of the extended AB hairpin will necessitate its close contact with a proteinase bound at the inhibitory site of TIMP-2 (see Fig. 1), this interaction need not contribute to the overall binding affinity in all cases and could, in some cases, conceivably weaken the overall binding interaction by making unfavorable contacts with the proteinase (6). The crystallographic data for the TIMP-2⅐MMP-14 complex have shown that the side chain of Tyr-36 is positioned on the surface of the MMP-14 catalytic domain in a cavity formed by the MT loop, the side chains of Asp-212 and Phe-180, and the S loop, which allows the formation of a hydrogen bond between the tyrosine hydroxyl group and the carboxylate oxygens of Asp-212 as well as with a number of Van der Waals contacts (4).…”
Section: Timp-2/mmp-14 Interactionssupporting
confidence: 76%
“…This finding further supports our previous suggestion that although the position of the extended AB hairpin will necessitate its close contact with a proteinase bound at the inhibitory site of TIMP-2 (see Fig. 1), this interaction need not contribute to the overall binding affinity in all cases and could, in some cases, conceivably weaken the overall binding interaction by making unfavorable contacts with the proteinase (6). The crystallographic data for the TIMP-2⅐MMP-14 complex have shown that the side chain of Tyr-36 is positioned on the surface of the MMP-14 catalytic domain in a cavity formed by the MT loop, the side chains of Asp-212 and Phe-180, and the S loop, which allows the formation of a hydrogen bond between the tyrosine hydroxyl group and the carboxylate oxygens of Asp-212 as well as with a number of Van der Waals contacts (4).…”
Section: Timp-2/mmp-14 Interactionssupporting
confidence: 76%
“…Because it was not possible to assign the NMR signals for the C-terminal region of RbpA, we cannot map the precise residues involved. It is not unusual for conformational averaging caused by protein flexibility to occur at high affinity protein-protein interaction sites; indeed there are many documented examples (52,(61)(62)(63)(64). The N and C termini are on the same side of the structured core (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier NMR studies on the interaction of N-TIMP-2 with cdMMP-3 indicated a key role of the sA-sB loop of TIMP-2 for binding specificity. 22 It is thus clear that the small sV-hB loop of MMP-13 allows a closer approach of the Cterminal subdomain towards the enzyme than the more exposed loop of MT1-MMP, and that the bulkier S-loop of MMP-13 enforces a deviation of the C-connector loop. Both contacts are in agreement with the overall tilt observed in the two TIMP-2 complexes.…”
Section: Interaction Between Mmp-13 and Timp-2mentioning
confidence: 98%